Genetics, Genome-Wide Association Studies, and Menarche - Witchel, Selma Feldman (Seminars in Reproductive Medicine, 2016)
Puberty is characterized by maturation of the hypothalamic–pituitary–gonadal axis, development of secondary sexual features, increased linear growth velocity, maturation of the epiphyses limiting additional growth, and achievement of menarche. The age at menarche appears to have a significant genetic component. With the advent of genome-wide association studies (GWASs), the genome has been interrogated to find associations between specific loci and age at menarche. It is apparent that multiple genetic loci, epigenetic mechanisms, and environmental factors modulate this biological event crucial for reproductive competence.
Keywords: age at menarche; puberty; GWAS; LIN28B